Evaluation of heat stress index associated with heat strain among workers in palm oil plantations - Wan Akmal, Wan Anuar (2025)
Heat Stress is one of the critical components that can affect human health particularly among workers due to exposure from hot environment. This study aims to evaluate the heat stress associated with heat strain level among palm oil plantation workers by assessing environmental heat stress, measuring workers’ heat strain level and determining the relationship between these variables. Using the combination measurements and questionnaires, environmental heat stress was identified by Wet Bulb Glob Temperature (WBGT) through parameters including ambient temperature, relative humidity and radiant heat. Workers’ heat strain level was assessed through a set of questionnaires that included worker characteristics, physical activity and perceived symptoms, perception of workplace ambient, working attire and personal protective equipment and workplace setting. The outcomes gained show that environmental heat stress in palm oil plantation sectors is high risk particularly during peak working hours which exceed the threshold limit value (TLV) recommended by American Conference of Governmental Industrial Hygienists (ACGIH). However, workers who experience heat stress are not impactful towards their heat strain level since the heat strain score index shows green zone (≤ 13.5) area which is considered safe. Therefore, the result obtained from this study is that there is no relationship between environmental heat stress and heat strain level among palm oil plantation workers. From the findings, the level of exposure heat exposure can be determined as high risk but not affect the workers heat strain. Thus, safe work practices can be maintained.